Managing diversity in the workplace: women’s conflicts between work and family life in China - Ru, Lina (2012)
For the past few decades, there has been numerous literature produced on managing diversity and great attention has been paid on the work life conflicts. However, not so many studies have investigated the Chinese women’s work life conflicts and the relationship between diversity and work life conflicts has not been fully discussed and explained, hence the main purpose of this study is to explore how a range of characteristics can influence Chinese women’s work life conflicts and come up with possible ways to minimize them. Findings show that personal life status influence the commitments employees face in their personal lives such as marital status and parental status. This study also indicated that Chinese women’s work life plight was greatly enhanced with the support of their family members, supervisor, colleagues or friends. Moreover, time-based conflict and strain-based conflict seem to be the major types of conflicts affecting Chinese women. In regard to how to cope with these conflicts, separating the boundary between work and life, keeping physiologically and psychologically healthy are the basic ways that most employees utilized.